2020
DOI: 10.1108/jcefts-04-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Country-of-origin as a dynamic concept: an analysis of Chinese consumer electronics brands in Germany

Abstract: Purpose Using consumer electronics brands as examples, this paper aims to present country-of-origin (COO) as a dynamic concept, by analyzing changes in the representation and perception of the “Made in China” label in Germany. Design/methodology/approach Building on previous COO research, the study formulates four research questions, which are answered with a comprehensive brand analysis using website, media, and consumer data. Information were collected from 11 Chinese brand websites, 10,681 German media ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…There has been only limited research analyzing how a country’s image evolves over time (e.g. Karimov and El-Murad, 2019; Polfuβ and Sönmez, 2020), which suggests that an assessment of longitudinal changes of country image can help offer insights on this question.…”
Section: Introductionmentioning
confidence: 99%
“…There has been only limited research analyzing how a country’s image evolves over time (e.g. Karimov and El-Murad, 2019; Polfuβ and Sönmez, 2020), which suggests that an assessment of longitudinal changes of country image can help offer insights on this question.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of major household shoppers in the Germany showed that participants believed that CoO indicated the country-of-origin of the product, not the country where the "last major change" occurred. In a comprehensive survey, only 12% of respondents accurately understood CoO label (defined as the place where the last major change in food occurred) [8,23]. Except for evaluating consumers' use of CoO labels, it is also necessary to evaluate consumers' understanding of CoO label information in order to formulate appropriate labeling regulations and public policy guidelines for F&V products [19].…”
Section: Introductionmentioning
confidence: 99%